G68 Mental health admissions to an acute paediatric ward. (12th March 2018) - Pierson, K; Merino Elia, A; Seregni, F; Takon, I; Govender, T
Abstract : Aims: 10% of children and young people in the UK have a diagnosable mental health problem. NICE Guidelines recommend that Acute Paediatric Services provide a place of safety for young people who present to A and E, while a mental health assessment takes place. The aim of this study was to evaluate the service and safety of children and young people with mental health problems admitted to our acute paediatric ward. Methods: We carried out a retrospective analysis of all CAMHS patients admitted to our acute paediatric ward, over a 3 month period. The study looked at reasons for presentation and admission, demographics, documentation of risk assessment, waiting time for an initial CAMHS assessment, presence of a one to one Registered Mental Health Nurse (RMN), documentation of observations, recurrence of admission for similar problem, length of stay, and outcome/follow up at discharge. Results: Patients were aged 11 to 17 years with 82% being female. Less than 30% had risk assessments and none had RMNs. 85% were admitted awaiting CAMHS assessment, of which 79% were previously known to CAMHS and 50% had previous mental health admissions to our paediatric ward. Not all patients had regular observations, with 33% having only an initial set of observations carried out. All except one had a CAMHS assessment within 24 hours of presentation and 74% of these were discharged within 24 hours. Three patients were transferred to an inpatient mental health unit. Conclusions: Children and young people with mental health problems constitute a significant percentage of admissions to paediatrics. Many of them are recurrent attenders known to CAMHS. Most of the patients were seen by CAMHS within 24 hours as per NICE guidelines. However, with poor documentation of risk assessments, no RMN presence, and scattered observations, there is a need for improvement to the safety of mental health admissions to acute paediatric wards.